JONAS HANWAY AND LOIS BAZIN ON NADIR SHAH’S DAGESTAN CAMPAIGN OF 1741-43 - Musaev, Mahac Abdulaevic; Abakarov, Ibragim Magomedovic (History, Archeology and Ethnography of the Caucasus, 2019)
A number of studies devoted to the campaigns of Nadir Shah in Dagestan were published in the form of monographs and articles, the preparation of which involved an extensive range of sources and diverse literature. However, some interesting information resources about the events of 1741-43 in Dagestan have not been properly studied. To such we can attribute the information of Europeans who visited the region in the 30s – 40s of the 18th century. Among those, who left written evidence, are an English traveler Jonas Hanway and a Frenchman Lois Bazin, who were well acquainted with each other. The first one published a four-volume collection, entitled “An historical account of the British trade over the Caspian Sea” (London, 1753). The fourth volume contains the information on Nadir Shah. The events of 1741-43 in Dagestan are given in Chapter XXIX. The translation of parts of the chapter is provided in this paper. The second of them, in a letter written in 1751, describes events he was an eyewitness to, since he was in Derbent at the time Nadir Shah arrived there. The article provides a translation of a fragment of the letter, published in the “Lettres edifiantes et curieuses” (Paris, 1780). The texts of Hanway and Bazin have much in common; some theses, although set out in different variations, are similar in meaning and subordinate to the same logic. However, Hanway’s text is noticeably more filled with facts and describes the Nadir’s Dagestan campaign wider. A comparative analysis of narratives shows that Bazin’s stories served as the main source for Hanway. At the same time, he had messages from Europeans in Russian and Persian service, from Russian military men and officials, as well as, possibly, Persian subjects, which allowed him to provide a more informative report.